Microclimate weather data for 1978 and 1979 at the University of Wisconsin-Milwaukee Field Station - (:unkn) unknown (My University, 1981)
The UWM Field Station has measured precipitation, temperature, relative humidity, wind direction and speed, and barometric pressure continuously since December 29, 1969. These data were recorded at three weather stations each located within a different vegetation type all within 0.8 km of each other. The main station is located near the Field Station laboratory building in an open field. This station measures all of the above parameters. The two satellite stations, one in a beech-maple forest and the other in a tamarack-white cedar bog, measure precipitation, temperature, and relative humidity only. This paper summarizes and compares the data collected at each station for the years 1978 and 1979. The results discussed are tentative since only two of the 11 years of data have been analyzed.
Keywords: microclimate; weather data